Swearing Words in Ambonese Malay and Batak Languages: Cross-Cultural Pragmatic Study - Hasan, Nita Handayani (Southeast Asian Language and Literature Studies, 2025)
The Batak and Ambonese ethnic groups are often perceived as distinct from other Indonesian communities due to their expressive communication style. Among them, the use of swearing is considered a normal part of social interaction, whereas members of other ethnic groups may perceive it as inappropriate. This study aims to identify the realization and types of swear words in the Batak language (Toba dialect) and Ambonese Malay within non-formal and family contexts, as well as to reveal the implicatures underlying these swearing speech acts. This study employed a qualitative descriptive design. The data consisted of swearing utterances collected from family and informal situations through direct interviews and the Discourse Completion Task (DCT) method. The DCT questions were designed to elicit implicatures embedded in the use of swearing. The findings indicate that both Ambonese Malay and Batak Toba contain swearing terms categorized into animals, objects, body parts, kinship, supernatural beings, activities, professions, states, and interjections. However, Ambonese Malay exhibits a greater number and variety of swearing expressions than Batak Toba. The implicatures found across both languages mainly convey annoyance, anger, and disappointment. In some cases, swearing without referents functions as a conversational diversion as well as an emotional outlet.